Sexual dimorphism in the methane seep-dwelling Costa Rican yeti crab Kiwa puravida (Decapoda: Anomura: Kiwaidae) - Azofeifa-Solano, Juan Carlos; Pereira, Olívia S.; Cowell, Emily Jayne; Cordes, Erik E.; Levin, Lisa A.; Goffredi, Shana K.; Cortés, Jorge (Frontiers in Marine Science, 2022)
Deep-sea chemosynthesis-based ecosystems support unique biological communities, but human impacts are an increasing threat. Understanding the life-history traits of species from deep-sea chemosynthesis-based ecosystems can help to develop adequate management strategies, as these can have impacts on ecological responses to changes in the environment. Here we examined the occurrence of sexual dimorphism in the yeti crab Kiwa puravida, an endemic species from the Costa Rican Pacific margin that aggregates at active methane seeps and depends on chemosynthetic bacteria for nutrition. The two morphological features examined included the claws, suspected to be under sexual selection and used for defense, and the carpus of the second pereopod not suspected to be under sexual selection. A total of 258 specimens, 161 males, 81 females, 16 juveniles, were collected from Mound 12 at 1,000-1,040 m depth in 2017 and 2018 and analyzed. We found that males have larger and wider claws than females, while there were no differences in carpus length. These results suggest that claw weaponry is under sexual selection in K. puravida, which is probably related to the mating system of this deep-sea species. This is the first attempt to study the reproductive biology of K. puravida, and additional observations will be necessary to shed more light on this matter.